SEDIMENT ORGANIC MATTER AND MAKROZOOBENTHOS ABUDANCE IN WATERS OF PURNAMA DUMAI - Gurning, Misael; Nedi, Syahril; Tanjung, Afrizal (Asian Journal of Aquatic Sciences, 2019)
This research was conducted at April 2019 in Waters of Purnama Dumai. The aim of the study was to analyze the content of organic sediment and macrozoobenthos abundance and the relationship of organic sediment with macrozoobenthos abundance. The method used was a survey method consisting of 4 stations with 3 replications at each station. Sampling was carried out in the field and then taken to the Marine Chemistry Laboratory for analysis of sediment and organic material fractions. The results showed that the average content of organic sediment material in Waters of Purnama Dumai is 66,47 % and the content of organic sediment material between different stations is not significantly different (P>0,05) while the abundance of macrozoobenthos is 32 ind/m2 and the abundance of macrozoobenthos between stations was not significantly different (P>0,05). The relationship between the organic matter content of sediments and the abundance of macrozoobenthos has a value (r) = 0,235797 which means it has a weak relationship